PRONUNCIATION PROBLEMS OF ENGLISH STOP SOUND MADE BY THE SECOND GRADERS OF SMA PANJURA MALANG - Ferdinanda Itu Meo; Yokie Prasetya Dharma (Journal of English Educational Study (JEES), 2019)
Pronunciation is the most important part in English. As we knows students are always marked by different activities, such as learning activities, private lessons, and course, students can learn better from these activities. This study is aimed to know the pronunciation problems of certain significant English stop sound among the second graders of SMA Panjura Malang and in what position of words the problems occur. This research was a qualitative desctiptive design. The instruments were 50 words, containing voiceless stop of /p/, /t/, /k/ in initial, medial, and final position; each contains five or six intended sounds in different position of words to test the students, and a cell phone to record the pronunciation of the students. The results showed that the most problematic sounds for the students were the aspirated consonants /p/, /t/, /k/ which appeared in initial, medial, and final positions of words. The comparison of both Indonesian and English for the most problematic words showed that one factor that might cause the pronunciation problems of English stop sounds are: (1) there are sounds in English which are phonemic, but they are not phonemic in Indonesian, (2) there are some sounds which do not exist Indonesian, but they exist in English, (3) there are sounds which are voiced in English but they are voiceless in Indonesian, (4) these are sounds pronounced with aspiration in English, but not in Indonesian. Another indication of the cause is the unfamiliarity of the students toward the words. The results are hoped to be the feedback for the teachers to give model in minimal pairs to the students and be able to improve the pronunciation problems of their students.Keywords; pronunciation, segmental sounds, voiceless stop, consonants.